UNDERSTANDING READINESS FOR DIABETES PREVENTION AND FACTORS AFFECTING LIFESTYLE CHANGE IN WOMEN WITH A HISTORY OF GESTATIONAL DIABETES MELLITUS IN SINGAPORE - SUMALI SUBHASHINI HEWAGE AKURASSA HEWAGE (2019)
Ph.D